Dostęp do informacji publicznej jako kategoria ochrony interesu prawnego jednostki na przykładzie wybranych regulacji odnoszących się do „stref specjalnych” - Tomaszewska, Katarzyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The need to guarantee the implementation of the protection of the legal interest is an element of the right to a democratic rule of law. The implementation of this type of protection is closely linked with the simultaneous aspiration of human respect of privacy and the need for social control authorities and other administrative bodies representing the authority of the state, even with the construction of access to public information; in particular, in this case, the actions of public bodies to each citizen individually. Not without significance, however, is also an element of social control of actions for the benefit of the general public. It is worth taking a look at the implementation of the universal right to information on the basis of the regulations devoted to “special zones”.
Keywords: ochrona jednostki; strefy specjalne; prawo do informacji; dostęp do informacji publicznej